Outlining Recent Trends in Australian Strategic Calculus vis a vis US-China Hegemonic Animosity - Iqbal, Sadia (Annals of Human and Social Sciences, 2024)
This study focused on analyzing the Australia’s policy vis a vis U.S.-china rivalry. The paper explores the nature of Australian policy vis a vis U.S. and China individually, and extrapolate Australia’s likely position in a hypothetical military confrontation between U.S. and China. Trends and shifts in Australia’s stated positon have been recorded and possible roles of new groupings such as Quad and AUKUS that might impact Australia’s future course of action have been analyzed. Australian policy appeared to be going through several periods of stasis and flux where Chinese dominance of the Far East became a dominant factor in shaping Australian orientation. However, over time, Australia appears to have changed course and fallen back into U.S. bloc in this emerging animosity. The overt Australian policy was reviewed through official publications while the opposite underlying currents were analyzed through review of historical events and research publications. Such a study would be informative for policy makers dealing with Australia and for scholars analyzing the ever-changing Far Eastern landscape. It was concluded that indeed Australian position has wavered somewhat in recent decades, nonetheless, it can finally now be safely concluded as a firm member of the U.S. bloc in the U.S.-China strategic competition.